Recovering Tomato Landraces to Simultaneously Improve Fruit Yield and Nutritional Quality Against Salt Stress - Massaretto, Isabel L.; Albaladejo, Irene; Purgatto, Eduardo; Flores, Francisco B.; Plasencia, Félix; Egea-Fernández, Jose M.; Bolarin, Maria C.; Egea, Isabel (Frontiers in Plant Science, 2018)
Salt stress generally induces important negative effects on tomato (Solanum lycopersicum) productivity but it may also cause a positive effect improving fruit quality, one of the greatest challenges in nowadays agriculture. Because of the genetic erosion of this horticultural species, the recovery of locally adapted landraces could play a very important role in avoiding, at least partially, production losses and simultaneously improving fruit quality. Two tomato landraces endemic of the Spanish Southeast area, characterized by the harsh climatic conditions of the Mediterranean basin, have been selected: Negro Yeste (NY) characterized by its dark-red colored fruits and Verdal (V), which fruits did not achieve the characteristic red color at ripening. Here the agronomic, physiological and metabolic responses of these landraces were compared with the reference tomato commercial cv. Moneymaker (MM), in plants grown without salt (control) and with salt stress (100 mM NaCl) for 70 days. The higher salt tolerance of both landraces was mainly reflected in the fruit number, as NY only reduced the fruit number in salt stress by 20% whereas in MM it was reduced till 43%, and in V the fruit number even showed an increase of 33%with salt stress. An important fruit quality parameter is soluble solids content, which increases induced by salinity were significantly higher in both landraces (60 and 78% in NY and V, respectively) compared with MM (34%). Although both landraces showed a similar response in relation to the high chlorophyll accumulation detected in their fruits, the fruit metabolic profiles were very different. Increased carotenoids levels were found in NY fruits, especially lycopene in ripe fruit, and this characteristic was observed in both control and salt stress. Contrarily, the carotenoid biosynthesis pathway was disrupted in V ripe fruits, but other metabolites, such as Ca2+, mannose, formate and glutamate were accumulated. These results highlight the potential of tomato landraces to improve nutritional fruit quality and maintain fruit yield stability under salt stress.